Model reference learning control for a class of nonlinear systems - Cheah, Chien Chern. (2009)
In the conventional learning control design, a desired output trajectory is specified and an iterative aigorithm is implemented to improve the tracking performance as the action is repeated. This limits the potential researches and applications of the learning controller because in some important tasks like impedance control of robotic manipulator, an explicit reference model is given rather than the desired trajectory. As a result, learning impedance control has not been studied in the force control and learning control of robotic manipulator.